Rekonstrukce továrny - Hnízdilová, Aneta Aya (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce řeší přestavbu stávajícího továrního objektu, který je dlouhodobě nevyužívaný – tzv. brownfield, na bydlení a komerční využití. Ve stávajícím prvním nadzemním podlaží budou realizovány po rekonstrukci kancelářské prostory, v nastavěném patře pak 4 bytové jednotky.

The thesis deals with the reconstruction of the existing factory building, which has long been unused - so-called brownfield, for housing and commercial use. On the first above-ground floor, offices will be reconstructed after the reconstruction, with 4 residential units on the second floor.
reconstruction of factories
Keywords: rekonstrukce; brownfield; továrna; změna užívání; reconstruction; brownfield; factory; change of use a building